PRO DAN KONTRA PANDANGAN PEGAWAI PENCATAT NIKAH (PPN) ATAS PERUBAHAN BATASAN USIA MINIMAL PERKAWINAN DALAM UNDANG-UNDANG NOMOR 16 TAHUN 2019 - Thiyas Tono Taufiq; Qotrunnada Zulfa Hafsari (Jurnal Asy-Syukriyyah, 2021)
This research focuses on discussing changes in the minimum age for marriage as stipulated in Law Number 16 of 2019 as an amendment to Law Number 1 of 1974 concerning marriage. The new Marriage Law changes the minimum marriage limit for men and women who will marry at least 19 years of age, previously the marriage limit for men is 19 years old and for women is 16 years old. This research seeks to find the pros and cons of legalizing the minimum age limit for marriage according to the views of the staff of the marriage register at the Office of Religious Affairs (KUA) in Yogyakarta who were non-randomly selected. The results of this research indicate that the process of changing the age limit of marriage does not see the pros and cons in society. Most importantly, the enactment of this law can hurt women, so that the purpose of reforming Islamic family law can realize legal unification by the times.